2022
DOI: 10.1186/s40069-022-00531-x
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Behavior of Low Calcium Fly Ash Based Geopolymer Reinforced Concrete Beam

Abstract: Pioneering studies have been conducted on alternative cementitious material in the manufacturing of conventional concrete to reduce carbon emission and improve the overall efficacy. However, there are limited studies on eco-friendly materials with low calcium fly ash. This study aims to examine the strength fly ash geopolymer concrete and reduce carbon emission. In this investigation, flexural test is done for conventional and geopolymer concrete (GPC) beam samples after the fulfillment of rest period and 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In general, the midspan deflections at 𝑃 𝑢 of GPC beams were 18% greater than OPC beams due to the lower stiffness of GPC beams than OPC beams with similar fc'. Alex et al [57] reported that GPC beams exhibited 9% greater midspan deflection than OPC beams. Zinkaah et al [22] also reported that midspan deflections of GPC beams were greater than OPC beams.…”
Section: Applied Loads (P U ) and Midspan Deflections Of Opc And Gpc ...mentioning
confidence: 99%
“…In general, the midspan deflections at 𝑃 𝑢 of GPC beams were 18% greater than OPC beams due to the lower stiffness of GPC beams than OPC beams with similar fc'. Alex et al [57] reported that GPC beams exhibited 9% greater midspan deflection than OPC beams. Zinkaah et al [22] also reported that midspan deflections of GPC beams were greater than OPC beams.…”
Section: Applied Loads (P U ) and Midspan Deflections Of Opc And Gpc ...mentioning
confidence: 99%
“…The primary objective is to compare the load-carrying capacity of cement and geopolymer concrete slabs under static and impact loading conditions. The strength of conventional concrete decreases when exposed to temperatures beyond 600°C, but by adding a higher percentage of nano silica fume, the strength of the concrete can be increased at high temperatures, improving its durability and performance [1]. Concrete undergoes changes in physical and chemical properties when subjected to high temperatures [2].…”
Section: Introductionmentioning
confidence: 99%
“…Portland cement-based concrete has become the second most widely used material worldwide after water, and it was expected that the global annual cement production would be 5.9 billion tons in 2020 [ 1 ]. Moreover, it's increased by 10% every year [ 2 ]. The massive production of Ordinary Portland Cement OPC, which consumes a lot of energy and natural resources, emits a lot of carbon dioxide CO2 into the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Among precursor materials, fly ash is the most popular source material that is used to produce GPC [ 4 , 14 , 22 ]. The utilisation of low-calcium fly ash-based GPC was recommended as a replacement for OPC concrete because it performed better and had fewer environmental disasters [ 2 ]. Fly-ash-based GPC shows many advantages.…”
Section: Introductionmentioning
confidence: 99%